Dendritic Cells and Their Role in Cardiovascular Diseases: A View on Human Studies - Maja-Theresa Dieterlen; Katja John; Hermann Reichenspurner; Friedrich W. Mohr; Markus J. Barten (Journal of Immunology Research)
The antigen-presenting dendritic cells (DCs) are key to the immunological response, with different functions ascribed ranging from cellular immune activation to induction of tolerance. Such immunological responses are involved in the pathophysiological mechanisms of cardiovascular diseases, with DCs shown to play a role in atherosclerosis, hypertension, and heart failure and most notably following heart transplantation. A better understanding of the interplay between the immune system and cardiovascular diseases will therefore be critical for developing novel therapeutic treatments as well as innovative monitoring tools for disease progression. As such, the present review will provide an overview of DCs involvement in the pathophysiology of cardiovascular diseases and how targeting these cells may have beneficial effects for the prognosis of patients.